Asthma and its association with cardiovascular disease in the elderly. The Cardiovascular Health Study Research Group. - Enright, P L; Ward, B J; Tracy, R P; Lasser, E C (J Asthma, 1996)
Cardiovascular disease (CVD) is more prevalent in elderly than in middle-aged patients. Symptoms such as intermittent wheezing with dyspnea may then be due to either CVD or asthma. The objective of this study was to determine the prevalence and correlates of asthma in the elderly and their associations with CVD and CVD risk factors. A community sample of 5201 elderly persons from the Cardiovascular Health Study was asked if they had a physician diagnosis of asthma, and multiple cardiovascular risk and disease variables were measured. Six percent of the participants (309) recalled a history of asthma, and half of these were never smokers. Thirty percent of those with asthma were currently taking a bronchodilator, 14% inhaled steroids, and 10% oral prednisone. Men and women with asthma who were cigarette smokers were more likely to report a concurrent diagnosis of congestive heart failure than smokers without asthma (p = .04). However, when we determined the independent CVD correlates of asthma in this cohort, controlling for smoking status, age, gender, and diagnoses of chronic bronchitis and emphysema, only higher levels of high-density lipoprotein cholesterol (HDL-C) and higher plasma fibrinogen levels were significantly associated with asthma. It was concluded that asthma is as prevalent in the elderly as in middle-aged persons and is associated with higher HDL-C and higher fibrinogen levels, but not with prevalent cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Asthma; Cardiovascular Diseases; Cohort Studies; Female; Humans; Lung; Male; Multivariate Analysis; Prevalence; Risk Factors; Sex Distribution; Smoking